Manajemen Keuangan Dalam Novel Tuan Direktur Karya Hamka - Deta Anjarwati; Naila Zahra Nurrahmi; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2023)
This research uses qualitative research using heuristic methods to build leadership in the novel Mr Director Hamka's work. The problem faced is the pressure in the business environment found in the novel Mr Director. The data source for this research was taken from the novelMr Director Based on this research, Hamka's work can be concluded that financial management, literary works and companies play an important role in running a company.